Gerenciamento para sistemas de armazenamento híbrido de energia para mitigação de intermitência em geração fotovoltaica - Pagnoncelli, Everton Luiz (2025)
This work addresses the impact of intermittent renewable energy sources on the electrical distribution system, exploring techniques to mitigate the challenges inherent to the nature of such sources. The main objective of the dissertation is to present a management approach for a hybrid storage system, composed of supercapacitors and batteries integrated with photovoltaic generation, aiming to reduce the effects of intermittency. The project includes a theoretical review of photovoltaic generation, power converters, energy storage technologies, and fuzzy logic. Subsequently, the application of fuzzy logic for the management of the hybrid storage system is proposed. The implementation is carried out in a real-time emulation environment using the Typhoon-HIL platform,allowing the validation of the system dynamics, along with the development of control loops and embedded management in a microcontroller. Finally, the system is evaluated in a daily photovoltaic generation scenario, in which an adaptive window moving average strategy is proposed for energy dispatch control.